2011
DOI: 10.1021/pr100969w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of P38 MAPK Pathway as a Molecular Signature in Ulcerative Colitis

Abstract: Early diagnosis and treatment of ulcerative colitis (UC) is clinically challenging. To overcome this problem, we explored the interrelated multiplex signaling pathway to identify molecular signatures in UC by using integrated strategy in proteomics. Intestinal mucosa of 12 UC cases and 12 normal controls underwent comparative proteomic analysis. A total of 26 unique differential proteins were identified, including 12 up-regulated and 14 down-regulated in UC group. A differential protein cluster, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 34 publications
(52 reference statements)
6
24
0
Order By: Relevance
“…Studies using tissue-specific conditional knockouts of p38a mice showed the importance of this isoform in the inflammatory response, both in cultured macrophages in vitro (8) and for development of skin and gut inflammation in vivo (9,10). p38a also mediates inflammation in IBD; it is highly phosphorylated and active in the inflamed intestinal mucosa of patients with IBD (11,12). The role of p38a in colitis was confirmed in experimental mouse models, and p38a/bMAPK inhibitors have been tested in clinical trials (10,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using tissue-specific conditional knockouts of p38a mice showed the importance of this isoform in the inflammatory response, both in cultured macrophages in vitro (8) and for development of skin and gut inflammation in vivo (9,10). p38a also mediates inflammation in IBD; it is highly phosphorylated and active in the inflamed intestinal mucosa of patients with IBD (11,12). The role of p38a in colitis was confirmed in experimental mouse models, and p38a/bMAPK inhibitors have been tested in clinical trials (10,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the p38 MAPK signal transduction pathway plays an important role in the inflammatory response. Rafiee et al (2002) found that p-p38MAPK was higher in IBD patients than in normal people, and positively correlated with the degree of intestinal inflammation (Zhao et al, 2011). Waetzig et al (2002) found that during IBD intestinal epithelial injury, the activity of p38MAPK was significantly increased, and revealed that by tissue immunohistochemistry high p38MAPK expression in macrophages and neutrophils of the intestinal lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial antibodies are used in our study: anti-COL1A2 (ab72637), anti-ATP4B (ab2866), and anti-HADSHC (ab54477). Proper validation of the ATP4B, COL1A2, and HADSHC antibodies used the same procedure as was described previously 24. The ICH was semi-quantitatively scaled in a range from “−” to “+++” by evaluating the representative tumor with intensity and percentage of cells showing significantly higher immune staining than normal matched-adjacent tissues.…”
Section: Methodsmentioning
confidence: 99%